Development of a system model for the functioning of distribution electrical supply systems in transport infrastructure projects - Kulbovskyi, Ivan; Holub, Halyna; Skliarenko, Inna; Bambura, Olga; Soloviova, Olena (Technology audit and production reserves, 2019)
The object of research is the power supply system of railway transport, which is part of a unified system and belongs to the class of geographically distributed electrical facilities. The main component of the system are electric networks, which represent a key technological chain of the transport process, provide it with energy, make up a significant part of the costs, connect geographically distributed objects and therefore represent one of the technological foundations for the integration of transport control. This significantly affects the efficiency of all links of the railway transport, which is especially important from the point of view of the corporate interests of the industry. In the course of the study, a systematic approach, system analysis methods, approaches to optimal production management with the support of the technological process of current repair and maintenance of electricity distribution systems were used. As well as ways of organizing a single information space of primary information that reflects the state of the power supply system. An information model of the control system for the processes of ongoing maintenance and repair is obtained, which will improve the efficiency of the control system already at the initial stages of their design. This is due to the fact that the proposed model has a number of features of the functioning and organization of repair work. In particular, the planning of the work of power distribution systems, operation, taking into account the optimization of repair work, management decisions, the interaction of the structural units of the power supply service based on set of problems Zjk. Thanks to this, it is possible to obtain information about individual processes of organizing the planning of the current maintenance and repair of the distribution system of power supply of structural units of the service. Compared with similar ones, this provides such advantages as the ability to register, transmit and process information in the power supply control mode. As well as the ability to implement periodic and occasional control and assessment of the reliability of the system, software and hardware and information, quick system analysis of various situations, the ability to form the most effective management decisions.